Features of Hemophagocytic Lymphohistiocytosis in Infants With Severe Combined Immunodeficiency: Our Experience From Chandigarh, North India - Vignesh, Pandiarajan; Anjani, Gummadi; Kumrah, Rajni; Singh, Ankita; Mondal, Sanjib; Nameirakpam, Johnson; Jindal, Ankur; Suri, Deepti; Sharma, Madhubala; Kaur, Gurjit; Sharma, Sathish; Gupta, Kirti; et al. (Frontiers in Immunology, 2022)
Background: Hemophagocytic lymphohistiocytosis (HLH) is characterized by uncontrolled and excessive inflammation leading to high mortality. Aetiology of HLH can be primary due to genetic causes or secondary due to infections or rheumatological illness. However, rarely T-cell deficiencies like severe combined immunodeficiency (SCID) can develop HLH. Objective: To describe clinical and laboratory features of SCID cases who developed HLH. Methods: We collected clinical, laboratory, and molecular details of patients with SCID who developed HLH at our centre at Chandigarh, North India. Results: Of the 94 cases with SCID, 6 were noted to have developed HLH-like manifestations. Male-female ratio was 5:1. Median (inter-quartile range) age of onset of clinical symptoms was 4.25 months (2-5 months). Median (inter-quartile range) delay in diagnosis was 1 month (1-3.5 months). Family history of deaths was seen in 4 cases. Molecular defects in IL2RG were seen in 5 out of 6 cases. Documented infections include disseminated bacillus calmette-guerin (BCG) infection (n=2), blood stream infections (n=3) with Staphylococcal aureus (n=1), Klebsiella pneumonia (n=1), and Pseudomonas aeruginosa (n=1), pneumonia (influenza H1N1 strain and K. pneumoniae (n=1)). Conclusion: Children with SCID can present with HLH-like manifestations secondary to fulminant infections. A high index of suspicion of SCID is needed in infants who present with HLH who have an associated infection or a suggestive family history. Occurrence of HLH-like manifestations in SCID suggests that T-lymphocytes may not have a significant role in immunopathogenesis of HLH.